Agricultural development addresses food loss and waste while reducing greenhouse gas emissions - Galford, Gillian L.; Peña, Olivia; Sullivan, Amanda K; Nash, Julie; Gurwick, Noel; Pirolli, Gillian; Richards, Meryl B.; White, Julianna M.; Wollenberg, Eva Karoline (Elsevier, 2020)
Food loss and waste (FLW) reduce food available for consumption and increase the environmental burden of production. Reducing FLW increases agricultural and value-chain productivity and may reduce greenhouse gas emissions associated with feeding the global population. Although studies of interventions that reduce FLW exist, almost no research systematically investigates FLW interventions across multiple value chains or countries, most likely due to challenges in collecting and synthesizing data and estimates, let alone estimating greenhouse gas emissions. Our research team investigated changes in FLW in projects supported by the United States Agency for International Development's (USAID) global hunger and food security initiative, Feed the Future. This was a unique opportunity to conduct ex-ante estimates of the impacts of FLW interventions across 20 value chains in 12 countries, based on project documents and interviews with USAID and project staff. This paper describes specific interventions in each value chain and country context, providing insight to interventions that decrease FLW at multiple points along food value chains, from upstream producer-dominated stages to downstream consumer-dominated stages. Amongst the sub-sectors studied, FLW interventions directed at extensive dairy systems could decrease FLW by 4–10%, providing meaningful greenhouse gas mitigation, since these systems are both emission-intensive and experience high FLW. More modest emissions reductions were found for other key agricultural products, including maize, rice, vegetables, fruits and market goods.